Fault Ride-Through Capability of DSTATCOM for Distributed Wind Generation System - Manju Aggarwal; Madhusudan Singh; S. K. Gupta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In this paper, fault ride through analysis of a low voltage distribution system augmented with distributed wind generation using squirrel cage induction generator and distribution static compensator (DSTATCOM) is carried out through modeling and simulation study in MATLAB. The impact of different types of unbalanced (single line to ground) fault in a low voltage distribution system in normal and severe conditions are studied and analysed in details. Analysis on system instability is also shown in case of sever fault condition. A distribution Static Compensator (DSTATCOM) is used to improve fault ride through (FRT) capability of wind generation system by compensating positive sequence voltage. A comparison of dynamic response of the system with and without DSTATCOM and effects of DSTATCOM on voltage and generator speed are presented. The simulation results shows that DSTATCOM is capable of reducing the voltage dips and improving the voltage profiles by providing reactive power support to distributed wind generation system under balanced as well as unbalanced faults condition and enhances the fault ride through capability of the wind generator